O‐GlcNAcylation stabilizes β‐catenin through direct competition with phosphorylation at threonine 41. Issue 8 (17th April 2014) - Stichelen, Stéphanie Olivier‐Van; Dehennaut, Vanessa; Buzy, Armelle; Zachayus, Jean‐Luc; Guinez, Céline; Mir, Anne‐Marie; Yazidi‐Belkoura, Ikram El; Copin, Marie‐Christine; Boureme, Didier; Loyaux, Denis; Ferrara, Pascual; Lefebvre, Tony
Abstract : Dysfunctions in Wnt signaling increase β‐catenin stability and are associated with cancers, including colorectal cancer. In addition, β‐catenin degradation is decreased by nutrient‐dependent O ‐GlcNAcylation. Human colon tumors and colons from mice fed high‐carbohydrate diets exhibited higher amounts of β‐catenin and O ‐GlcNAc relative to healthy tissues and mice fed a standard diet, respectively. Administration of the O ‐GlcNAcase inhibitor thiamet G to mice also increased colonic expression of β‐catenin. By ETD‐MS/MS, we identified 4 O ‐GlcNAcylation sites at the N terminus of β‐catenin (S23/T40/T41/T112). Furthermore, mutation of serine and threonine residues within the D box of β‐catenin reduced O ‐GlcNAcylation by 75%. Interestingly, elevating O ‐GlcNAcylation in human colon cell lines drastically reduced phosphorylation at T41, a key residue of the D box responsible for β‐catenin stability. Analyses of β‐catenin O ‐GlcNAcylation mutants reinforced T41 as the most crucial residue that controls the β‐catenin degradation rate. Finally, inhibiting O ‐GlcNAcylation decreased the β‐catenin/α‐catenin interaction necessary for mucosa integrity, whereas O ‐GlcNAcase silencing improved this interaction. These results suggest that O ‐GlcNAcylation regulates not only the stability of β‐catenin, but also affects its localization at the level of adherens junctions. Accordingly, we propose that O ‐GlcNAcylation of β‐catenin is a missing link between the glucose metabolism deregulation observed in metabolic disorders and the development of cancer.—Olivier‐Van Stichelen, S., Dehennaut, V., Buzy, A., Zachayus, J.‐L., Guinez, C., Mir, A‐M., El Yazidi‐Belkoura, I., Copin, M.‐C., Boureme, D., Loyaux, D., Ferrara, P., Lefebvre, T. O ‐GlcNAcylation stabilizes β‐catenin through direct competition with phosphorylation at threonine 41. FASEB J. 28, 3325–3338 (2014). www.fasebj.org